PELAKSANAAN KEGIATAN PROMOTIF SANTUN LANSIA DI PUSKESMAS KECAMATAN CILINCING, JAKARTA UTARA PADA TAHUN 2019 - Astuti, Diantri; Fawzi, Indra Lestari (UI Scholars Hub, 2021)
The elderly diseases are generally degenerative diseases, the handling requires a long time and high costs, so that it will be a very heavy burden for the government. The Puskesmas Santun Lansia is a health center that provides comprehensive health services to the elderly population, which includes promotive, curative, preventive, and rehabilitative services. Health care for the elderly give priority to quality promotion and prevention. This study aims to evaluate the process of implementing the promotional activities of Santun Lansia at the Cilincing District Health Center and what are the supporting and inhibiting factors in the implementation of this activity. This research is a formative evaluation research on the Promotional Activities of Santun Lansia which is still running until the end of 2019. This research uses a qualitative research approach with purposive and snowball techniques sampling. The informants of this study consisted of program Staff at the Puskesmas, Elderly Cadres, and Elderly Assistants. Data collection was carried out through document and literature search, observation, and in-depth interviews. The results of this study indicate that the implementation of promotional activities at the Santun Lansia Community Health Center in 2019 has gone according to plan and is felt to be useful by the elderly and it is hoped that it can continue.